Pyroptosis in sepsis: Comprehensive analysis of research hotspots and core genes in 2022 - Xia, Demeng; Wang, Sheng; Yao, Renqi; Han, Yuexue; Zheng, Liyu; He, Pengyi; Liu, Ying; Yang, Lu (Frontiers in Molecular Biosciences, 2022)
Sepsis, a life-threatening disease caused by dysregulated host response to infection, is a major public health problem with a high mortality and morbidity rate. Pyroptosis is a new type of programmed cell death discovered in recent years, which has been proved to play an important role in sepsis. Nevertheless, there is no comprehensive report, which can help researchers get a quick overview and find research hotspots. Thus, we aimed to identify the study status and knowledge structures of pyroptosis in sepsis and summarize the key mechanism of pyroptosis in sepsis. The data were retrieved and downloaded from the WOS database. Software such as VOSviewer was used to analyze these publications. Key genes were picked out by using (https://www.genecards.org) and (http://www.bioinformatics.com). Then, Gene Ontology (GO) enrichment analysis and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis were used to performed these key genes. From 2011 to 2021, a total of 299 papers met the search criteria, and the global interest in pyroptosis in sepsis measured by the value of (RRI) has started to increase since 2016. China ranked first in the number of publications, followed by the USA. The journal Frontiers in Immunology published the most relevant articles. Through keyword co-occurrence analysis, the high-frequency subject terms were divided into three clusters like “animal research”, “cell research,” and “molecular research” clusters. “mir,” “aki,” “monocyte,” and “neutrophil” were the newest keywords that may be the hotspot. In addition, a total of 15 genes were identified as hub genes. TNF, IL-1β, AKT1, CASP1, and STAT3 were highly expressed in lung tissues, thymus tissues, and lymphocytes. KEGG analysis indicated that pyroptosis may play a vital role in sepsis via the NOD, PI3K/AKT, and MAPK/JNK pathways. Through the quantitative analysis of the literature on pyroptosis in sepsis, we revealed the current status and hotspots of research in this field and provided some guidance for further studies.